Effects of aqueous extract of Origanum vulgare L. (Lamiaceae) on the preimplantational mouse embryos - Benavides, Víctor (2010)
The use of medicinal plants for the treatment of illnesses is widely known. However, there are not many scientific reports about the properties of these plants and their side effects. In this study, the effect of the aqueous extract of Origanum vulgare on the preimplantational mouse embryo development was investigated. The oregano aqueous extract was given ad libitum to four separated groups (n= 10) of pregnant mice: O, 9, 18 y 36 mg/mL respectively. When the embryos were evaluated, a slight delay in the embryo development was observed, but only with the highest dose. With respect to embryo quality, an increase of degenerated embryos was observed but this was not significant. These results showed that the aqueous extract of O. vulgare does not have a toxic effect on preimplantational mouse embryo, and it only produces a slight delay in embryo development.